Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Which recursive formula can be used to generate the sequence shown, where [tex]f(1) = 5[/tex] and [tex]n \geq 1[/tex]?

[tex]5, -1, -7, -13, -19, \ldots[/tex]

A. [tex]f(n+1) = f(n) + 6[/tex]

B. [tex]f(n) = f(n+1) - 6[/tex]

C. [tex]f(n+1) = f(n) - 6[/tex]

D. [tex]f(n+1) = -6f(n)[/tex]


Sagot :

To determine the appropriate recursive formula for the sequence [tex]\(5, -1, -7, -13, -19, \ldots \)[/tex], we need to observe how the terms change from one to the next.

First, let's note the initial values:
- The first term [tex]\( f(1) \)[/tex] is 5.

Next, let's find the difference between each consecutive term:
- The difference between the second term and the first term: [tex]\(-1 - 5 = -6\)[/tex].
- The difference between the third term and the second term: [tex]\(-7 - (-1) = -7 + 1 = -6\)[/tex].
- The difference between the fourth term and the third term: [tex]\(-13 - (-7) = -13 + 7 = -6\)[/tex].
- The difference between the fifth term and the fourth term: [tex]\(-19 - (-13) = -19 + 13 = -6\)[/tex].

We see that the sequence consistently decreases by 6 at each step. This means that to get the next term, we subtract 6 from the current term.

Therefore, the recursive formula that fits this pattern is:
[tex]\[ f(n+1) = f(n) - 6 \][/tex]

This means the correct formula to generate the given sequence is:
[tex]\[ \boxed{f(n+1) = f(n) - 6} \][/tex]